Economic accounting and high-tech strategy for sustainable production: A case study of methanol production from CO2 hydrogenation. (22nd July 2022) - Su, Chenqing; Wei, Haoran; Wang, Zhanao; Ayed, Hamdi; Mouldi, Abir; Shayesteh, Ali Akbar
Abstract: The global proposal of 'carbon neutrality' puts forward higher innovation demand for the cleaner energy production. The potential for employing "green" methanol produced from hydrogen obtained by water electrolysis and collected CO2 from a gas-fired power station is examined in this study. The consumption of electricity for renewable methanol production is 1.045 times as much as that for traditional methanol production, the traditional method consumes 2.5 times as much thermal energy as the renewable methanol process. In addition, the total direct and indirect CO2 emissions from renewable methanol production are almost one-third of the emissions from the traditional method. The total cost of setting up the units of a renewable and a traditional methanol production plant with an annual capacity of 100, 000 tons is $50.1 million and $46.806 million in this study case, respectively. If the methanol price hits $310 per ton, renewable methanol production will be highly economically viable. But if electricity and gas prices rise or CO2 emission tax is imposed, renewable and conventional methanol production plants will lose their economic feasibility. Therefore, in order to deal with this risk, the establishment of special high-tech parks is of great significance to reduce costs and stabilize the sustainable development of relevant industries. Highlights: Introducing a new methanol synthesize plant from CO2 hydrogenation. Techno-economic assessments of the introduced plant and propose the construction idea of high-tech park. The sustainable-based methanol synthesize is compared to the conventional methanol production method.